DIGITAL DOMINANCE: EXPLORING THE REASONS BEHIND THE WANING POPULARITY OF PRINT MEDIA - Dash, Raimohan; Ghosh, Ramkrishna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In a time when digital technology rules, the print media sector has changed dramatically. Print media, which was once seen as the main source of news and information, has had to change and reinvent itself to thrive in the digital era. This article examines the different ways that print media has changed, including the advent of online publications, the fall of traditional newspapers, and the creation of new hybrid models.